Economics - What Is A "Have Not" Nation (The 1968 Jackling Lecture) - Francis Cameron (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Gloomy predictions that domestic mineral reserves are approaching exhaustion are unwarranted and may be harmful, this author contends. Specific mineral forecasting errors in the Paley Report are cited to support this contention, and steps that can be taken to insure a progressive mineral industry capable of keeping pace with the major raw material needs of the nation through advancing technology are suggested. Mining is both exciting and rewarding —although at times somewhat frustrating— and we all can have real pride in our industry, in its people, and in its accomplishments. It is, however, with concern that I have noted a deterioration in this Country in what might be called mining's stature and in the growth of a belief in many quarters that our mineral reserves are rapidly approaching exhaustion. In other words, there is a popular image that we are fast becoming a "have not" nation in many respects and that the domestic mining industry can no longer be considered, in the vernacular of Wall Street to offer much in the way of "growth potential." I do not subscribe to this hypothesis, nor do I be-li4ve that the record of the mining industry bears this out. However, let me add that we can, in time, talk ourselves into this frame of mind and we can hasten the day when this very well might come about by unnecessary and unwise legislation or regulation. My remarks today are basically designed to give my reasons for refuting this negative philosophy and to review our record. With your help, I know we can improve our image, and the public's recognition of our industry's peculiar problems. The progress of our civilization over the centuries has been fundamentally based upon proper use of raw materials, both agricultural and mineral, and upon energy, human or otherwise. As the standard of living has progressed century by century, the demands for mineral raw materials have increased in an irregular, but steadily rising progression. Fortunately, those minerals on which we depend most, i.e., iron, coal, petroleum, copper, aluminum, lead, and zinc have been neither too difficult to find nor to process into useful form. Iron, the most useful of all metals, is present in various amounts in most rock types and soils. Gold, seemingly the most generally desired (but certainly not the most useful of all metals), occurs in sea water in a far greater total tonnage than has been won from all of the world's known gold mines. If the latter is true, then why do we not see large installations treating sea water for the recovery of its gold content? The answer, of course, is that even the French, who seem, from their recent actions, to value gold above all else, have not devised a way of doing this at a profit. Theoretically, it is possible, but not with today's technology at a cost which would justify the effort. Man has exploited only those mineral concentrations which accidents of nature have placed within his so far limited means of finding and utilizing. What we geologists and engineers refer to as an orebody is nothing more than a concentration of minerals, exploitable with available knowledge, that will yield a value greater than the value attached to the energy and capital required to produce it. What is "ore" and what is not "ore" is, in the end, a matter of economics. The economic problem stems from the physical and chemical character of mineral deposits. The good Lord stacked the cards heavily in favor of rising costs by limiting the amount of the higher grade ores easily available. As the best and most accessible ores are depleted, it becomes necessary to work harder and with greater ingenuity to produce more from less accessible and lower grade resources. The quantity of mineral raw materials we can have in the future will be determined largely by what we can afford to pay for them in terms of human effort, capital outlay and production energies. We will always have the problem of cost with us and our only real means of keeping ahead of rising costs is by continually improving our technical abilities. We, in this country at least, no longer have open to us large and unexplored virgin wildernesses in which a pick-and-shovel prospector might uncover an untouched mineral bonanza. The rest of the world also has few conventional frontiers left in which the explorer-prospector is free to roam. We do, however, have enormous land areas unexplored, and untouched po-